Study on acupuncture in the treatment of painful diabetic peripheral neuropathy based on rs-fMRI: a protocol for systematic review and meta-analysis - Guan Wang; Mengyuan Li; Yanze Liu; Jiazhen Cao; Lin Yao; Haipeng Huang; Haizhu Zheng; Hongfeng Wang (BMJ Open)
Introduction Studies have shown that acupuncture has significant therapeutic effects on painful diabetic peripheral neuropathy (PDPN) yet the precise mechanism of action underpinning these effects remains controversial. Resting-state functional MRI (rs-fMRI) is an advanced imaging technique that can be used to monitor changes in the activity of the brain, particularly in PDPN. However, the data from several studies remain inconclusive and there is currently no systematic review and meta-analysis for the use of rs-fMRI in PDPN.Methods and analysis In this study, we will select all eligible studies published on or before 30 June 2021. Four English and four Chinese databases will be searched, specifically, PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, WanFang database, China Science Technology Journal Database (VIP) and China Doctor/Master Dissertations Full-text Database. Only clinical trials and the first cycle of a cross-over trial linked to acupuncture for PDPN will be included in the analysis. The main outcomes include the amplitude of low-frequency fluctuation, regional homogeneity, functional connectivity of the brain, bilateral superficial peroneal nerve sensory nerve conduction velocity, bilateral dorsal current perception threshold values and the degree of subjective pain. The secondary outcomes include biochemical indicators, the degree of depression and anxiety and changes in efficiency. The study selection, data extraction and risk of bias assessment will be performed by two investigators. For statistical analyses, Review Manager V.5.4 software will be used. If necessary, heterogeneity testing, data synthesis, and subgroup analysis will be performed.Ethics and dissemination Our systematic review and meta-analysis will be based on published literature for data extraction and will not include the use of individual patient data and so no ethical approval required.PROSPERO registration number CRD42021211644.